Satisfaction of Peruvian university students with distance education - Jurado-Enriquez, Elizabeth Lizbel (2024)
The satisfaction of university students is a crucial aspect in the educational environment, as it influences their academic experience, emotional well-being, and academic performance. Understanding the factors that contribute to student satisfaction is fundamental to improve the quality of higher education and promote an environment conducive to learning and personal development. The purpose is to analyze the satisfaction of Peruvian university students with distance education; the study is quantitative, cross-sectional, and descriptive, conducted in a private university in the region of Ica in Peru, among 139 students. A questionnaire of sociodemographic, academic, and labor variables was used, with the scale of satisfaction with virtual courses (SVC-S). A descriptive and bivariate analysis was carried out; as for the results, 25,2% were dissatisfied and 74,8% were satisfied with taking their classes through the virtual modality. According to the statistical analysis revealed that there are no significant differences with the sociodemographic, academic, and labor variables (p>.05). Thus, students agree with the virtual modality because it fits their needs.